Acquisition of antibiotic resistance by Staphylococcus aureus in skin patients. Issue 12 (December 1978) - Naidoo, J; Noble, W C
Abstract : Acquisition of resistance to neomycin, gentamicin, fusidic acid, or clindamycin has been observed in three strains of Staphylococcus aureus and data from three patients infected with these strains are presented in detail. Clindamycin resistance followed the expected pattern by appearing in a strain of Staph. aureus with dissociated resistance to erythromycin after treatment with erythromycin and clindamycin. Low-level resistance to fusidic acid appeared in two strains in the apparent absence of exposure to that antibiotic. Labile neomycin resistance was encountered in a previously sensitive strain after topical neomycin therapy. Gentamicin resistance appeared in all three strains after topical therapy. In all three strains, a labile resistance (presumably plasmid-mediated) occurred with minimum inhibitory concentrations (MICs) of 64-128 microgram/ml but in one strain a stable resistance with MIC over 3000 microgram/ml appeared.